Analisis Kemampuan Literasi Spasial Pada Materi Mengenal Peta Siswa Kelas IV SDN 060921 Medan - Demmina Ginting; Dian Armanto; Anita Yus (STKIP Subang, 2026)
The problem in this research lies in the lack of students' spatial literacy skills in the material